A century of change: Reconstructing the biogeochemical history of Hubbard Brook. Issue 6 (16th June 2021) - Likens, Gene E.; Buso, Donald C.; Bernhardt, Emily S.; Rosi, Emma
Abstract: Ecosystems constantly adjust to altered biogeochemical inputs, changes in vegetation and climate, and previous physical disturbances. Such disturbances create overlapping 'biogeochemical legacies' affecting modern nutrient mass balances. To understand how 'legacies' affected watershed‐ecosystem (WEC) biogeochemistry during five decades of studies within the Hubbard Brook Experimental Forest (HBEF), we extended biogeochemical trends and hydrologic fluxes back to 1900 to provide an historical framework for our long‐term studies. This reconstruction showed acid rain peaking at HBEF in the late 1960s‐early 1970s near the beginning of the Hubbard Brook Ecosystem Study (HBES). The long‐term, parabolic arc in acid inputs to HBEF generated a corresponding arc in the ionic strength of stream water, with acid inputs generating increased losses of H + and soil base cations between 1963 and 1969 and then decreased losses after 1970. Nitrate release after disturbance is coupled with previous N‐deposition and storage, biological uptake, and hydrology. Sulfur was stored in soils from decades of acid deposition but is now nearly depleted. Total exports of base cations from the soil exchange pool represent one of the largest disturbances to forest and associated aquatic ecosystems at the HBEF since the Pleistocene glaciation. Because precipitation inputs of base cations currently are extremely small, such losses can only be replaced through the slow process of mineral weathering. Thus, the chemistry of stream water is extremely dilute and likely to become even more dilute than pre‐Industrial Revolution estimates. The importance of calculating chemical fluxes is clearly demonstrated in reconstruction of acid rain impacts during the pre‐measurement period. The aggregate impact of acid rain on WEC exports is far larger than historical forest harvest effects, and even larger than the most severe deforestation experiment (Watershed 2) at HBEF. A century of acid rain had a calcium stripping impact equivalent to two W2 experiments involving complete deforestation and herbicide applications.